German HR-Managers in the Wake of the Global Crisis. Humble Hangmen or Intelligent Problem Solvers? - Karl-Friedrich Ackermann (Human Resource Management, 2010)
The objective of this article is to study the behavior of German HR managers in the wake of the global crisis. Some criticize them as humble hangmen who simply execute the orders of top management—killing jobs and laying off people. Others praise them as intelligent problem solvers who did an excellent job in mastering the crisis without causing mass unemployment. Based on an inquiry among leading HR managers as well as on statistical facts and figures, four questions are posed: (1) How did HR managers see themselves in the face of crisis challenges? (2) Which tools did they apply to master the crisis? (3) Are there any long–term megatrends that determine HRM during and after a global crisis? (4) What present and future priorities do the managers have? Numerous documents and other material of varying quality are available to answer these questions. Only a rough overview, however, is given below in order not to go beyond the scope of this article. Though the database used is country–specific and refers only to Germany, some general trends and issues have been observed, which might prove relevant in international knowledge transfer. – – Mit Blick auf die Finanz- und Wirtschaftskrise 2008/2009, die Deutschland als exportorientiertes Land in besonderer Weise getroffen hat, werden u.a. die Ergebnisse einer empirischen Studie zur Rolle der Personalleiter in der globalen Krise vorgestellt, die irgendwo zwischen den Extrempositionen ,,Henker“, der hauptsächlich Mitarbeiter entlässt und ,,Intelligenter Problemlöser“, der Entlassungen nach Möglichkeit zu vermeiden versucht, angesiedelt sein wird. Das ermittelte Selbstverständnis der Personalleiter und die Analyse der von ihnen verwendeten Instrumente zur Bewältigung der Krise, lassen rückblickend den Schluss zu, dass die Personalleiter sich ganz überwiegend dem Rollentyp des ,,Intelligenten Problemlösers“ entsprechend verhalten haben. Dafür spricht auch der intelligente Umgang mit einigen langfristigen Megatrends wie z.B. ,,demografischer Wandel“, ,,Technologischer Wandel“, ,,Globalisierung“ etc., die neue Lösungen für das Personalmanagement erfordern.
Keywords: M5; 650; Rolle der Personalleiter; Krisenmanagement; Krisenmanagement; Personalabbau; Personalbestand; Personalplanung; Arbeitskräfte